2020
DOI: 10.3390/jcm9123959
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on Hysterectomy by Vaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES) Compared to Laparoscopic Hysterectomy for Benign Indications

Abstract: (1) Objective: We aimed to report an update of the systematic review and meta-analysis by Baekelandt et al. (2016). (2) Method: We followed PRISMA guidelines to perform this systematic review. We searched MEDLINE, EMBASE, CENTRAL and additional sources and aimed to retrieve randomised controlled trials (RCTs), controlled clinical trials (CCTs) and prospective/retrospective cohort studies in human subjects that allowed direct comparison of vNOTES to laparoscopy. (3) Results: Our search yielded one RCT and five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 16 publications
(55 reference statements)
3
50
1
Order By: Relevance
“…This is the first study to analyze vaginal pain separately from abdominal pain. Contrary to the findings of this study, several studies have reported significantly lower postoperative pain in the vNOTES group than in the laparoscopy group [2,4,8,13]. On the other hand, previous studies that evaluated postoperative pain between laparoscopic and vaginal hysterectomy have reported higher postoperative pain in vaginal hysterectomy [12,14].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is the first study to analyze vaginal pain separately from abdominal pain. Contrary to the findings of this study, several studies have reported significantly lower postoperative pain in the vNOTES group than in the laparoscopy group [2,4,8,13]. On the other hand, previous studies that evaluated postoperative pain between laparoscopic and vaginal hysterectomy have reported higher postoperative pain in vaginal hysterectomy [12,14].…”
Section: Discussioncontrasting
confidence: 99%
“…A recent systematic review and meta-analysis that compared vNOTES hysterectomy to laparoendoscopic single-site (LESS) approach for benign indications yielded outcomes of one randomized controlled trial and five retrospective cohort trials [8]. Although vNOTES hysterectomy showed significantly shorter operation time and decrease in estimated blood loss, there were no differences in operative complications and postoperative pain scores.…”
Section: Introductionmentioning
confidence: 99%
“…10 Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) provides better exposure/access to pelvic organs, avoids trocar site complications, reduces pain scores, resulting in early hospital discharge, improves patient and cosmetic outcomes, with no visible abdominal scars. 11,12 Given its prominent advantages, using vNOTES as a day care procedure can increase the acceptance rate of opportunistic BS by more women. This study aimed to compare the transvaginal natural orifice approach versus conventional laparoscopy (CL) in opportunistic BS alone for permanent female sterilization as an opportunistic cancer prevention strategy.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, also vNOTES hysterectomy has undergone a strict validation pathway over the last decade. Recently, a metanalysis was performed by Housmans et al [4], including the data retrieved from one RCT and five retrospective studies about vNOTES hysterectomy compared to Laparoscopic Assisted Vaginal Hysterectomy (LAVH) and Total Laparoscopic Hysterectomy (TLH). One the one hand, data analysis was in favor of the vNOTES approach in terms of surgery duration and blood loss; on the other hand, no significant differences were reported regarding intra-and post-operative complications, pain scores and modification of hemoglobin levels evaluated on postoperative day 1.…”
mentioning
confidence: 99%